Estimation of economic welfare gains from trade facilitation in the Andean Community - Glenn P. Jenkins; Mehmet Nazif (Queen's University, Department of Economics, 2023)
Border procedures around the globe can act as barriers hindering international trade. Another impact of these procedures relates to their economic resource costs. In this study, using a microeconomic framework of international trade, the potential economic gains are estimated for reductions in trade administration costs related to sea border trade in the Andean Community (CAN) as well as for the increase in import and export trades that are stimulated as a consequence of the reduction in trade administration costs. The potential cost reductions are estimated separately for import and export trade. The estimates are made with respect to the existing levels of trade flows. We measure the excess economic cost of the current trade administration procedures in CAN with respect to two benchmark levels of trade administration costs, namely those for Chile and Singapore. Our results suggest that improving the trade administration cost levels to match those of the reference countries will enable CAN countries to enjoy economic resource savings of between US1.25 billion and US 1.5 billion annually, corresponding to 0.19% to 0.23% of their gross domestic product. Given the current trade environment of CAN nations, relevant policy and reform options are suggested. The key policy recommendation is to improve the electronic single window system for trade administration and in particular, the interconnectivity of information flows between the member countries of CAN. Maintaining the port infrastructure is also critical for the delivery of efficient services for the movement of goods.
Keywords: F14; F13; D60; 330; international trade; trade facilitation; trade administration cost; trade transaction costs; economic gain; welfare gain; Andean Community; Latin America